PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI Di KANTOR UPTD PENDIDIKAN KECAMATAN PELEPAT HILIR KABUPATEN BUNGO - -, ILYAS MADI (MENARA EKONOMI, 2015)
Office UPTD Pelepat Ilir Bungo district had planned to send 14 employees to participate in education and training. With the implementation of education and training to employees UPTD Office Pelepat Ilir Bungo district is expected to improve the performance of employees is seen from the quantity of work, quantity of work and job performance in the job.Based on the background and the extent of the problem mentioned above, the formulation of the problem in this study is: "How much influence and relationships of Education and Training on Employee Performance in Office UPTD Pelepat Ilir Bungo district?"The result showed that the coefficient of correlation or relationship education and training Against Increasing Employee Performance in the office of District UPTD Pelepat Ilir Bungo sometimes conducted by 0.946. Artinya is that education and training have a very Strong positive relationships and influence 0.894 or 89.4%. Means indicates that education and training has a very positive effect, while the remaining 10.6% is influenced by other variables not examined in this study.Based on the conclusions that the authors have described, the authors provide advice to the employee as follows: 1) the employee is expected to always improve education and Palatihan menikuti quickly as possible because it can improve the performance of employees in the days to come. And 2) Expected to Maintain Employee Performance The performance boost employees or more for the future.